Magnesium phosphate-polyurethane composite moisture-curing cold patch asphalt mixture and preparation method thereof

By using magnesium phosphate-polyurethane composite wet curing technology in cold-soft asphalt mixture, a synergistic complementary system between magnesium phosphate gelling material and polyurethane is formed, which solves the problem of slow curing speed of cold-soft asphalt mixture in humid environments, and the high strength and long-life effect after road repair is achieved.

CN119874325APending Publication Date: 2025-04-25CHINA GEZHOUBA GRP HIGHWAY OPERATION CO LTD +2

Patent Information

Application Number
CN202510095066.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing cold-added asphalt mixture has slow curing speed and insufficient early strength and stability in humid environments, resulting in low quality of road repair and short service life.

Method used

Magnesium phosphate-polyurethane composite wet curing cold-added asphalt mixture is used to form a synergistic complementary system with the polyurethane cured body through magnesium phosphate gelling material to improve the curing speed and early strength.

Benefits of technology

In humid environments, the curing speed, early strength and stability of the cold-added asphalt mixture are significantly improved, ensuring that the road surface after road repair has good durability and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874325A_ABST
    Figure CN119874325A_ABST
Patent Text Reader

Abstract

The invention discloses a magnesium phosphate-polyurethane composite type moisture-curing cold patch asphalt mixture and a preparation method of the magnesium phosphate-polyurethane composite type moisture-curing cold patch asphalt mixture. The modified asphalt is prepared from the following components in percentage by weight: 6.5 to 8.5 percent of matrix asphalt, 1 to 3 percent of magnesium phosphate cementing material, 1.5 to 3.5 percent of polyurethane, 0.1 to 0.5 percent of silane coupling agent, 0.3 to 1 percent of liquid SBS (Styrene Butadiene Styrene), 0.1 to 1 percent of coagulant, 1.5 to 4 percent of chain extender, 1.7 to 4 percent of diluent and 75 to 87 percent of aggregate. The preparation method comprises the following steps: preparing a magnesium phosphate cementing material, and preparing a moisture-curing prepolymer and liquid SBS (Styrene Butadiene Styrene); melting the matrix asphalt, and shearing and stirring the matrix asphalt and the diluent to obtain diluted matrix asphalt; shearing and stirring the moisture-cured prepolymer, a silane coupling agent, liquid SBS (Styrene Butadiene Styrene) and diluted matrix asphalt together to obtain asphalt cold supplementing liquid; and sequentially putting the aggregate of each grade of particle size, the asphalt cold patch and the magnesium phosphate cementing material into a mixer, and stirring to obtain the magnesium phosphate-polyurethane composite moisture-curing cold patch asphalt mixture. The curing speed, the early strength and the stability of the cold patch asphalt mixture can be improved in a humid environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of road construction material design and preparation, and specifically relates to a magnesium phosphate-polyurethane composite wet-curing cold-patch asphalt mixture and a preparation method thereof. Background Art

[0002] With the rapid development of urban construction in my country, the traffic volume has increased dramatically, and road construction has developed rapidly, especially the mileage of expressways and second-level and above roads has reached one million kilometers. The extensive road network plays a key role in economic development, regional exchanges and people's lives. With the continuous growth of my country's economic construction, higher requirements will be put forward for the quality, performance, maintenance and transportation efficiency of road construction in the future.

[0003] In the process of road construction and maintenance, the performance of road repair materials has an important impact on the service life and driving safety of roads. The road repair materials in the prior art mainly include hot-mix asphalt mixture and cold-patch asphalt mixture, and both road repair materials have certain defects. Hot-mix asphalt mixture needs to be heated on site during repair, which not only increases the maintenance cost and labor intensity, but also is greatly affected by weather and temperature. During the repair process, a high construction temperature needs to be maintained. It is mostly used to repair the road surface in summer. If it is repaired in a low temperature environment, it is difficult to achieve the ideal compaction and strength, resulting in the early damage of the repaired road surface; in addition, hot-mix asphalt mixture will produce a large amount of smoke and harmful gases during the repair process, causing environmental pollution. Cold-patch asphalt mixture has far greater advantages than hot-mix asphalt mixture in terms of environmental adaptability, repair procedures, material storage and transportation, and does not produce high-temperature harmful gases. It is currently the preferred material for road repair; however, when using cold-patch asphalt mixture to repair the road surface in a humid environment, due to its slow curing speed and insufficient strength development, the repaired road surface is prone to early damage, thereby affecting the repair quality and service life of the road.

[0004] At present, in the production process of cold patch asphalt mixture, polyurethane, as a polymer with lower cost than epoxy resin, has been widely used. However, the strength of polyurethane after curing is low and cannot meet the repair requirements of heavy-duty traffic asphalt pavement. Especially in humid environment, although polyurethane can be cured after contact with water, the curing speed is slow and the strength development is insufficient, which seriously affects the pavement repair effect and service life. Therefore, it is urgent to develop a magnesium phosphate-polyurethane composite wet-cured cold patch asphalt mixture and preparation method, through the magnesium phosphate gelling material and the polyurethane solid body to form a complementary system, so as to achieve the effect of improving the curing speed, early strength and stability of cold patch asphalt mixture in humid environment.

[0005] The invention patent with application publication number CN113248938A discloses a wet curing polyurethane modified cold mix asphalt and its preparation method, wherein the cold mix asphalt comprises the following raw materials in parts by weight: 60-75 parts of base asphalt, 10-20 parts of solvent, 5-15 parts of polyurethane prepolymer, 2-5 parts of plasticizer, 1-4 parts of desiccant, 1-3 parts of stabilizer, and 0.5-1.5 parts of wet curing agent. This technical solution accelerates the strength formation and improves the stability by adding polyurethane prepolymer and wet curing agent, but the curing speed of polyurethane is slow, the strength development is insufficient, and the road repair effect still needs to be improved.

[0006] The invention patent with application publication number CN117024054A discloses a reactive dilution type regenerated cold patch material suitable for use in severe rain and snow environments and its preparation method. The cold patch material includes the following raw materials by mass: 97-99 parts of asphalt pavement recycled material, 1-3 parts of mineral powder, 1-1.5 parts of fiber, and 4-6 parts of cold patch asphalt; the cold patch asphalt is made of asphalt, asphalt diluent, polyurethane, slaked lime and cement, and the mass ratio is asphalt: asphalt diluent: polyurethane: slaked lime: cement = 100: 25-32: 3-6: 2-5: 2-5. This technical solution modifies the cold patch liquid by adding polyurethane, cement and slaked lime, thereby improving the early strength and water stability of the cold patch material, but the curing speed of polyurethane is slow, the strength development is insufficient, and the pavement repair effect still needs to be improved. Summary of the invention

[0007] In order to solve the problems existing in the prior art, the present invention provides a magnesium phosphate-polyurethane composite wet-curing cold patch asphalt mixture, wherein the mass percentage of each substance in the cold patch asphalt mixture is 6.5-8.5wt% of base asphalt, 1-3wt% of magnesium phosphate gelling material, 1.5-3.5wt% of polyurethane, 0.1-0.5wt% of silane coupling agent, 0.3-1wt% of liquid SBS, 0.1-1wt% of accelerator, 1.5-4wt% of chain extender, 1.7-4wt% of diluent, 75-87wt% of aggregate, and the sum of the contents of each substance is 100wt%.

[0008] Preferably, the amount of the diluent added increases with the amount of the base asphalt added. Within the mass percentage range of the diluent and the base asphalt, the amount of the diluent added increases by 0.4-0.8wt% for every 0.5wt% increase in the amount of the base asphalt added.

[0009] In any of the above schemes, it is preferred that the sum of the added amounts of the coagulant and the chain extender increases with the increased added amount of the polyurethane, and within the mass percentage range of the coagulant, the chain extender and the polyurethane, when the added amount of the polyurethane increases by 0.5wt%, the sum of the added amounts of the coagulant and the chain extender increases by 0.6-1wt% accordingly.

[0010] In any of the above schemes, it is preferred that the mass percentage of each substance in the magnesium phosphate gelling material is 50-55wt% of dead-burned magnesium oxide, 18-24wt% of diammonium phosphate, 10-16wt% of fly ash, and 10-16wt% of aluminum oxide, and the sum of the contents of each substance is 100wt%.

[0011] In any of the above schemes, it is preferred that the particle size distribution of the dead-burned magnesium oxide is between 2-10 μm; the particle size distribution of the diammonium phosphate is between 30-100 μm, wherein the mass percentage of each particle size in the diammonium phosphate is as follows: 75-100 μm accounts for 35 wt%, 50-75 μm accounts for 35 wt%, and 30-50 μm accounts for 30 wt%; the particle size distribution of the fly ash is between 20-100 μm, wherein the mass percentage of each particle size in the fly ash is as follows: 75-100 μm accounts for 35 wt%, 50-75 μm accounts for 35 wt%, and 20-50 μm accounts for 30 wt%; the particle size distribution of the aluminum oxide is between 0.5-10 μm.

[0012] In any of the above schemes, it is preferred that the polyurethane is an adhesive synthesized from diphenylmethane-4,4'-diisocyanate as the main material; the silane coupling agent is γ-aminopropyltriethoxysilane and / or vinyltriethoxysilane; the mass percentage of each substance in the liquid SBS to the liquid SBS is 40-70wt% of solid SBS and 30-60wt% of organic solvent, and the organic solvent includes any one or more of toluene, cyclohexane, and acetone.

[0013] In any of the above schemes, it is preferred that the base asphalt is No. 70 base asphalt and / or No. 90 base asphalt; the accelerator includes any one or more of triethylamine, N,N-dimethylcyclohexylamine, and bis(dimethylaminoethyl) ether; the chain extender includes any one or more of 1,4-butanediol, neopentyl glycol, ethylene glycol, diethylene glycol, and 1,4-cyclohexanedimethanol; the diluent includes any one or more of diesel, kerosene, gasoline, solvent oil, aromatic oil, and xylene.

[0014] In any of the above schemes, it is preferred that the aggregate includes five particle sizes, and the mass percentage of each particle size in the aggregate is: particle size 13.2-16mm accounts for 10-15wt%, particle size 9.5-13.2mm accounts for 25-30wt%, particle size 4.75-9.5mm accounts for 25-30wt%, particle size 2.36-4.75mm accounts for 20-25wt%, particle size 0-2.36mm accounts for 10-15wt%, and the aggregate includes any one or more of limestone, basalt, granite, and diabase.

[0015] The present invention also provides a method for preparing a magnesium phosphate-polyurethane composite wet-curing cold-patch asphalt mixture, which is used to prepare the magnesium phosphate-polyurethane composite wet-curing cold-patch asphalt mixture described in any one of the above items, and comprises the following steps in order:

[0016] Step 1: Weigh all raw materials according to the designed material ratio;

[0017] Step 2: preparing magnesium phosphate gelling material according to the designed material ratio and process parameters;

[0018] Step 3: Put the aggregates of each particle size into the oven for drying. After the drying process is completed, reduce the temperature in the oven to a certain temperature, and keep the aggregates of each particle size at the reduced temperature for later use;

[0019] Step 4: Put the matrix asphalt into a container, and then put the container containing the matrix asphalt into an oven for heating to completely melt the matrix asphalt; after the heating is completed, take out the container containing the matrix asphalt from the oven, and put the completely melted matrix asphalt and the diluent into a high-speed shearing machine for shearing and stirring until the matrix asphalt and the diluent are completely melted to obtain diluted matrix asphalt;

[0020] Step 5: Put polyurethane, coagulant and chain extender into a container and mix them evenly to obtain a moisture-curable prepolymer; put solid SBS and organic solvent into another container and mix them evenly to obtain liquid SBS;

[0021] Step 6: Put the wet curing prepolymer, silane coupling agent and liquid SBS into a high-speed shearing machine, and shear and stir them together with the diluted matrix asphalt until they are completely blended to obtain asphalt cold patch liquid;

[0022] Step seven: Put the dried aggregates of various particle sizes into a mixer for stirring. After stirring for a certain period of time, while keeping the stirring speed unchanged, put the asphalt cold patch liquid into the mixer and continue stirring. After stirring for a certain period of time, increase the stirring speed and put the magnesium phosphate gel material into the mixer and continue stirring to obtain a magnesium phosphate-polyurethane composite wet-curing cold patch asphalt mixture.

[0023] Preferably, in step 2, the method for preparing the magnesium phosphate gelling material comprises the following steps in order:

[0024] Step (1): according to the designed material ratio, heavy-burned magnesium oxide and aluminum oxide are placed in a mixer and stirred at room temperature, a stirring speed of 100-200 r / min, and a stirring time of 60-90 s;

[0025] Step (2): according to the designed material ratio, fly ash of various particle sizes is placed in a mixer and continuously stirred at room temperature, a stirring speed of 200-300 r / min, and a stirring time of 90-150 s;

[0026] Step (3): according to the designed material ratio, diammonium dihydrogen phosphate of each particle size is placed in a mixer and continuously stirred. The stirring temperature is room temperature, the stirring speed is 200-300 r / min, and the stirring time is 90-150 s. After the stirring is completed, a mixture of the substances is obtained;

[0027] Step (4): placing the mixture of the substances into an oven for low-temperature drying, the drying temperature being 80-100° C., and the drying time being 1-2 h. After the drying process is completed, a magnesium phosphate gelling material is obtained, which is sealed for later use.

[0028] In any of the above schemes, it is preferred that in step three, the drying temperature of aggregates of various particle sizes is 100-120°C, and the drying time is 2-3h; the temperature in the oven is reduced to 60-80°C, that is, the insulation temperature of aggregates of various particle sizes is 60-80°C.

[0029] In any of the above schemes, it is preferred that in step four, the heating temperature of the base asphalt is 130-150°C, and the heating time is 1-2h; the shear stirring speed of the base asphalt and the diluent is 1500-2000r / min, and the shear stirring time is 0.5-1h.

[0030] In any of the above schemes, it is preferred that in step six, the shear stirring speed of the moisture-curing prepolymer, silane coupling agent, liquid SBS and diluted matrix asphalt is 1500-2000 r / min, and the shear stirring time is 20-30 min.

[0031] In any of the above schemes, it is preferred that in step seven, the stirring speed of the aggregates of each particle size after drying is 400-500r / min, and the stirring time is 60-90s; the asphalt cold make-up liquid is put into the mixer and continued to be stirred at a speed of 400-500r / min, and the stirring time is 60-90s; the magnesium phosphate cementitious material is put into the mixer and continued to be stirred at a speed of 500-800r / min, and the stirring time is 90-150s.

[0032] In the present invention, the oven, high-speed shearing machine, mixer, etc. used are all traditional equipment, and there are no special requirements for the equipment structure and model. It is only necessary to ensure that several key parameters such as drying temperature, drying time, stirring speed, stirring time, etc. meet the requirements of the present invention.

[0033] In the present invention, the aggregate includes five particle sizes, namely, particle size 13.2-16mm, particle size 9.5-13.2mm, particle size 4.75-9.5mm, particle size 2.36-4.75mm, and particle size 0-2.36mm, that is, 13.2mm≤particle size<16mm, 9.5mm≤particle size<13.2mm, 4.75mm≤particle size<9.5mm, 2.36mm≤particle size<4.75mm, and 0mm≤particle size<2.36mm. The particle size distribution of dead-burned magnesium oxide is between 2-10μm, that is, 2μm≤particle size≤10μm. The particle size distribution of aluminum oxide is between 0.5-10μm, that is, 0.5μm≤particle size≤10μm. The particle size distribution of ammonium dihydrogen phosphate is between 30-100μm, including three particle sizes, namely, particle size 75-100μm, particle size 50-75μm, and particle size 30-50μm, that is, 75μm≤particle size≤100μm, 50μm≤particle size<75μm, and 30μm≤particle size<50μm. The particle size distribution of fly ash is between 20-100μm, including three particle sizes, namely, particle size 75-100μm, particle size 50-75μm, and particle size 20-50μm, that is, 75μm≤particle size≤100μm, 50μm≤particle size<75μm, and 20μm≤particle size<50μm. For each particle size, the material passes through the upper and lower sieve holes in sequence to obtain a particle size between the upper and lower sieve holes, for example: the particle size is 4.75-9.5mm (4.75mm≤particle size<9.5mm), that is, the material passes through the 9.5mm sieve hole and the 4.75mm sieve hole in sequence to obtain a particle size between 4.75-9.5mm.

[0034] In the present invention, the silane coupling agent is selected from γ-aminopropyl triethoxysilane and / or vinyl triethoxysilane, γ-aminopropyl triethoxysilane is KH550 model, and vinyl triethoxysilane is A151 model. Solid SBS is a styrene-butadiene-styrene block copolymer, and linear SBS or star SBS can be selected according to actual use.

[0035] In the preparation process of the cold patch asphalt mixture of the present invention, the selection of each substance, the mass percentage of each substance, the order of addition of each substance, the process parameters of each step, etc. are very important. At the same time, in the preparation process of the magnesium phosphate cementitious material, the selection of each substance, the mass percentage of each substance, the order of addition of each substance, the process parameters of each step, etc. are also very important. The various formula parameters and process parameters need to work synergistically to achieve the expected technical effect of the present invention.

[0036] In the present invention, magnesium phosphate gelling material and polyurethane solidification form a synergistic and complementary system. The magnesium phosphate gelling material prepared according to the material ratio and process parameters of the present invention has a rapid curing effect, its hydration reaction is rapid, and heat is released during the hydration reaction, which provides additional heat for the curing of polyurethane; polyurethane is wet cured by reacting with water in a humid environment, and the excess water generated by polyurethane during the reaction process can be used by the magnesium phosphate gelling material to accelerate its curing process; the temperature increase caused by the heat release of the magnesium phosphate gelling material reaction will further promote the curing reaction of polyurethane, because the curing speed of polyurethane is positively correlated with temperature. This synergistic and complementary effect of magnesium phosphate gelling material and polyurethane not only improves the overall curing speed of cold patch asphalt mixture, but also ensures that it has high performance in a humid environment, so that it can quickly meet the use requirements in road repair, while having good durability and stability. In addition, adding silane coupling agent and liquid SBS according to the material ratio of the present invention can further assist the formation of a synergistic and complementary system between magnesium phosphate gelling material and polyurethane.

[0037] The magnesium phosphate-polyurethane composite wet-curing cold-patch asphalt mixture and preparation method of the present invention have the following beneficial effects:

[0038] (1) The present invention forms a complementary system by using magnesium phosphate gelling material and polyurethane solid body, which can achieve the effects of improving the curing speed, early strength and stability of cold patch asphalt mixture in a humid environment.

[0039] (2) The cold patch asphalt mixture prepared by the present invention can be quickly cured in a humid environment, is not affected by moisture, and has high strength and stability after curing, thereby solving the problems of slow curing speed, low strength and insufficient development of traditional cold patch asphalt mixture in a humid environment.

[0040] (3) The cold patch asphalt mixture prepared by the present invention has excellent wet curing performance and high strength stability, and is suitable for road repair under various climatic conditions, especially for effective road repair in humid environments, which improves the flexibility and adaptability of construction, while ensuring that the repaired road surface has good stability and durability in humid environments.

[0041] (4) The present invention proposes for the first time an innovative idea of ​​adding magnesium phosphate gelling material, and designs the material ratio and preparation process of magnesium phosphate gelling material. The magnesium phosphate gelling material designed by the present invention can improve the strength and stability of cold patch asphalt mixture, and the magnesium phosphate gelling material forms a synergistic and complementary effect with polyurethane, which can make the cold patch asphalt mixture have higher strength after curing, can withstand greater traffic loads, extend the service life of the road, reduce the number of road maintenance and repairs, and have higher economic benefits.

[0042] (5) The cold patch asphalt mixture of the present invention does not require heating during the construction process, which reduces energy consumption and the emission of harmful gases and is environmentally friendly. At the same time, the use of magnesium phosphate cementitious materials and polyurethane also meets environmental protection requirements, reduces pollution to the environment, and conforms to the concept of modern green construction.

[0043] (6) The cold patch asphalt mixture of the present invention is more suitable for quickly repairing potholes, cracks, damages and other defects on highways or urban roads. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 It is a process flow chart of a preferred embodiment of the magnesium phosphate-polyurethane composite wet-curing cold-patch asphalt mixture and preparation method according to the present invention;

[0045] Figure 2 for Figure 1 A physical photograph of the magnesium phosphate gel material prepared in the embodiment shown;

[0046] Figure 3 for Figure 1 Microscopic morphology photograph of the cold patch asphalt mixture prepared in the embodiment shown after curing for 1 hour;

[0047] Figure 4 To adopt Figure 1 Photos of the cold patch asphalt mixture prepared in the embodiment shown are used to repair damaged roads, wherein: (a) is the state during repair, (b) is the state after 24 hours of repair, (c) is the state after 15 days of repair, and (d) is the state after 30 days of repair. DETAILED DESCRIPTION

[0048] In order to further understand the content of the present invention, the present invention will be described in detail below in conjunction with specific embodiments.

[0049] Embodiment 1:

[0050] According to a preferred embodiment of the magnesium phosphate-polyurethane composite wet-curing cold patch asphalt mixture of the present invention, the mass percentage of each substance in the cold patch asphalt mixture is 6.5wt% of base asphalt, 1wt% of magnesium phosphate gelling material, 1.5wt% of polyurethane, 0.1wt% of silane coupling agent, 0.6wt% of liquid SBS, 0.1wt% of accelerator, 1.5wt% of chain extender, 1.7wt% of diluent and 87wt% of aggregate.

[0051] The amount of the diluent added increases with the amount of the base asphalt added. Within the mass percentage range of the diluent and the base asphalt, when the amount of the base asphalt added increases by 0.5wt%, the amount of the diluent added increases by 0.4-0.8wt% accordingly. In this embodiment, the base asphalt and the diluent are both added in minimum amounts.

[0052] The sum of the added amounts of the coagulant and the chain extender increases with the increase in the added amount of the polyurethane. Within the mass percentage range of the coagulant, the chain extender and the polyurethane, when the added amount of the polyurethane increases by 0.5wt%, the sum of the added amounts of the coagulant and the chain extender increases by 0.6-1wt% accordingly. In this embodiment, the polyurethane, the coagulant and the chain extender are all added in minimum amounts.

[0053] The mass percentages of various substances in the magnesium phosphate gelling material are as follows: 53 wt % of dead-burned magnesium oxide, 21 wt % of diammonium phosphate, 13 wt % of fly ash and 13 wt % of aluminum oxide. The particle size distribution of the dead-burned magnesium oxide is between 2-10 μm; the particle size distribution of the diammonium phosphate is between 30-100 μm, wherein the mass percentage of each particle size in the diammonium phosphate is as follows: 75-100 μm accounts for 35 wt%, 50-75 μm accounts for 35 wt%, and 30-50 μm accounts for 30 wt%; the particle size distribution of the fly ash is between 20-100 μm, wherein the mass percentage of each particle size in the fly ash is as follows: 75-100 μm accounts for 35 wt%, 50-75 μm accounts for 35 wt%, and 20-50 μm accounts for 30 wt%; the particle size distribution of the aluminum oxide is between 0.5-10 μm.

[0054] The polyurethane is an adhesive synthesized from diphenylmethane-4,4'-diisocyanate as the main material; the silane coupling agent is γ-aminopropyltriethoxysilane; the mass percentage of each substance in the liquid SBS is 55wt% of solid SBS and 45wt% of organic solvent, and the organic solvent is toluene. The base asphalt is No. 70 base asphalt; the coagulant is triethylamine; the chain extender is 1,4-butanediol; and the diluent is diesel.

[0055] The aggregate includes five particle sizes, and the mass percentage of each particle size in the aggregate is: particle size 13.2-16mm accounts for 12wt%, particle size 9.5-13.2mm accounts for 27wt%, particle size 4.75-9.5mm accounts for 27wt%, particle size 2.36-4.75mm accounts for 22wt%, and particle size 0-2.36mm accounts for 12wt%. The aggregate is limestone.

[0056] like Figure 1 As shown, this embodiment also provides a method for preparing a magnesium phosphate-polyurethane composite wet-curing cold-patch asphalt mixture, which is used to prepare the above-mentioned magnesium phosphate-polyurethane composite wet-curing cold-patch asphalt mixture, and includes the following steps in order:

[0057] Step 1: Weigh all raw materials according to the designed material ratio;

[0058] Step 2: preparing magnesium phosphate gelling material according to the designed material ratio and process parameters;

[0059] Step 3: Put the aggregates of each particle size into the oven for drying. After the drying process is completed, reduce the temperature in the oven to a certain temperature, and keep the aggregates of each particle size at the reduced temperature for later use;

[0060] Step 4: Put the matrix asphalt into a container, and then put the container containing the matrix asphalt into an oven for heating to completely melt the matrix asphalt; after the heating is completed, take out the container containing the matrix asphalt from the oven, and put the completely melted matrix asphalt and the diluent into a high-speed shearing machine for shearing and stirring until the matrix asphalt and the diluent are completely melted to obtain diluted matrix asphalt;

[0061] Step 5: Put polyurethane, coagulant and chain extender into a container and mix them evenly to obtain a moisture-curable prepolymer; put solid SBS and organic solvent into another container and mix them evenly to obtain liquid SBS;

[0062] Step 6: Put the wet curing prepolymer, silane coupling agent and liquid SBS into a high-speed shearing machine, and shear and stir them together with the diluted matrix asphalt until they are completely blended to obtain asphalt cold patch liquid;

[0063] Step seven: Put the dried aggregates of various particle sizes into a mixer for stirring. After stirring for a certain period of time, while keeping the stirring speed unchanged, put the asphalt cold patch liquid into the mixer and continue stirring. After stirring for a certain period of time, increase the stirring speed and put the magnesium phosphate gel material into the mixer and continue stirring to obtain a magnesium phosphate-polyurethane composite wet-curing cold patch asphalt mixture.

[0064] In step 2, the preparation method of the magnesium phosphate gelling material comprises the following steps in order:

[0065] Step (1): according to the designed material ratio, put the dead-burned magnesium oxide and aluminum oxide into a mixer and stir them at room temperature, a stirring speed of 150 r / min, and a stirring time of 75 s;

[0066] Step (2): according to the designed material ratio, fly ash of various particle sizes is placed in a mixer and stirred continuously at room temperature, a stirring speed of 250 r / min, and a stirring time of 120 s;

[0067] Step (3): according to the designed material ratio, diammonium dihydrogen phosphate of each particle size is placed in a mixer and continued to be stirred. The stirring temperature is room temperature, the stirring speed is 250r / min, and the stirring time is 120s. After the stirring is completed, a mixture of the substances is obtained. Step (4): the mixture of the substances is placed in an oven for low-temperature drying. The drying temperature is 90°C and the drying time is 1.5h. After the drying treatment is completed, a magnesium phosphate gelling material is obtained and sealed for use.

[0068] In step three, the drying temperature of aggregates of various particle sizes is 110°C, and the drying time is 2.5h; the temperature in the oven is reduced to 70°C, that is, the insulation temperature of aggregates of various particle sizes is 70°C.

[0069] In step 4, the heating temperature of the base asphalt is 140°C, and the heating time is 1.5 hours; the shear stirring speed of the base asphalt and the diluent is 1800 r / min, and the shear stirring time is 0.8 hours.

[0070] In step six, the shear stirring speed of the moisture-curing prepolymer, silane coupling agent, liquid SBS and diluted matrix asphalt is 1800 r / min, and the shear stirring time is 25 min.

[0071] In step seven, the stirring speed of the aggregates of each particle size after drying is 450 r / min, and the stirring time is 75 s; the asphalt cold make-up liquid is put into the mixer and continued to be stirred at a stirring speed of 450 r / min and a stirring time of 75 s; the magnesium phosphate cementitious material is put into the mixer and continued to be stirred at a stirring speed of 650 r / min and a stirring time of 120 s.

[0072] In this embodiment, the magnesium phosphate gelling material prepared is as follows Figure 2 As shown in Figure 2, the microstructure of the prepared cold patch asphalt mixture after curing for 1 hour is as follows: Figure 3 The state of the road damage repaired by the cold patch asphalt mixture prepared in this embodiment is as shown in Figure 4As shown, (a) is the state during repair, (b) is the state after 24 hours of repair, (c) is the state after 15 days of repair, and (d) is the state after 30 days of repair. It can be seen from the figure that the asphalt cold patch material is firmly bonded in the cracks without falling off, is integrated with the original road surface, and has a smooth surface.

[0073] The magnesium phosphate-polyurethane composite wet-curing cold-patch asphalt mixture and preparation method of this embodiment have the following beneficial effects:

[0074] (1) By forming a complementary system between magnesium phosphate cementitious materials and polyurethane solidified bodies, the curing speed, early strength and stability of cold-patch asphalt mixtures can be improved in humid environments. (2) The prepared cold-patch asphalt mixture can be quickly cured in a humid environment, is not affected by moisture, and has high strength and stability after curing. (3) For the first time, an innovative idea of ​​adding magnesium phosphate cementitious materials was proposed, and the material ratio and preparation process of magnesium phosphate cementitious materials were designed; the designed magnesium phosphate cementitious materials can improve the strength and stability of cold-patch asphalt mixtures, and the magnesium phosphate cementitious materials and polyurethane form a synergistic and complementary effect, which can make the cold-patch asphalt mixture have a higher strength after curing, can withstand a large traffic load, extend the service life of the road, and reduce the number of road maintenance and repairs. (4) The cold-patch asphalt mixture does not need to be heated during the construction process, which reduces energy consumption and the emission of harmful gases and is environmentally friendly.

[0075] Embodiment 2:

[0076] According to another preferred embodiment of the magnesium phosphate-polyurethane composite wet-curing cold patch asphalt mixture and preparation method of the present invention, its material ratio, preparation process, technical principle, beneficial effects, etc. are basically the same as those of the first embodiment, except that:

[0077] The mass percentage of each substance in the cold patch asphalt mixture is as follows: 7wt% of base asphalt, 1.5wt% of magnesium phosphate cementitious material, 2wt% of polyurethane, 0.5wt% of silane coupling agent, 0.3wt% of liquid SBS, 0.4wt% of accelerator, 2wt% of chain extender, 2.3wt% of diluent and 84wt% of aggregate.

[0078] The amount of the diluent added increases with the amount of the base asphalt added. Within the mass percentage range of the diluent and the base asphalt, when the amount of the base asphalt added increases by 0.5wt%, the amount of the diluent added increases by 0.6wt% accordingly, and is controlled within the range of 0.4-0.8wt%.

[0079] The sum of the added amounts of the coagulant and the chain extender increases with the increased added amount of the polyurethane. Within the mass percentage range of the coagulant, the chain extender and the polyurethane, when the added amount of the polyurethane increases by 0.5wt%, the sum of the added amounts of the coagulant and the chain extender increases by 0.8wt% accordingly, and is controlled within the range of 0.6-1wt%.

[0080] The mass percentages of various substances in the magnesium phosphate gelling material are as follows: 50wt% of dead-burned magnesium oxide, 18wt% of diammonium phosphate, 16wt% of fly ash, and 16wt% of aluminum oxide. The particle size distribution of the dead-burned magnesium oxide is between 2-10 μm; the particle size distribution of the diammonium phosphate is between 30-100 μm, wherein the mass percentage of each particle size in the diammonium phosphate is as follows: 75-100 μm accounts for 35 wt%, 50-75 μm accounts for 35 wt%, and 30-50 μm accounts for 30 wt%; the particle size distribution of the fly ash is between 20-100 μm, wherein the mass percentage of each particle size in the fly ash is as follows: 75-100 μm accounts for 35 wt%, 50-75 μm accounts for 35 wt%, and 20-50 μm accounts for 30 wt%; the particle size distribution of the aluminum oxide is between 0.5-10 μm.

[0081] The polyurethane is an adhesive synthesized from diphenylmethane-4,4'-diisocyanate as the main material; the silane coupling agent is γ-aminopropyltriethoxysilane; the mass percentage of each substance in the liquid SBS is 40wt% of solid SBS and 60wt% of organic solvent, and the organic solvent is toluene. The base asphalt is No. 70 base asphalt; the coagulant is triethylamine; the chain extender is 1,4-butanediol; and the diluent is diesel.

[0082] The aggregate includes five particle sizes, and the mass percentage of each particle size in the aggregate is: particle size 13.2-16mm accounts for 10wt%, particle size 9.5-13.2mm accounts for 25wt%, particle size 4.75-9.5mm accounts for 25wt%, particle size 2.36-4.75mm accounts for 25wt%, and particle size 0-2.36mm accounts for 15wt%. The aggregate is limestone.

[0083] In step 2, the preparation method of the magnesium phosphate gelling material comprises the following steps in order:

[0084] Step (1): according to the designed material ratio, heavy-burned magnesium oxide and aluminum oxide are placed in a mixer and stirred at room temperature, a stirring speed of 100 r / min, and a stirring time of 90 s;

[0085] Step (2): according to the designed material ratio, fly ash of various particle sizes is placed in a mixer and stirred continuously at room temperature, a stirring speed of 200 r / min, and a stirring time of 150 s;

[0086] Step (3): according to the designed material ratio, diammonium dihydrogen phosphate of each particle size is placed in a mixer and continuously stirred. The stirring temperature is room temperature, the stirring speed is 200 r / min, and the stirring time is 150 s. After the stirring is completed, a mixture of the substances is obtained. Step (4): the mixture of the substances is placed in an oven for low-temperature drying. The drying temperature is 80° C. and the drying time is 2 h. After the drying is completed, a magnesium phosphate gelling material is obtained and sealed for later use.

[0087] In step three, the drying temperature of aggregates of various particle sizes is 100°C, and the drying time is 3h; the temperature in the oven is reduced to 60°C, that is, the insulation temperature of aggregates of various particle sizes is 60°C.

[0088] In step 4, the heating temperature of the base asphalt is 130°C, and the heating time is 2 hours; the shear stirring speed of the base asphalt and the diluent is 1500 r / min, and the shear stirring time is 1 hour.

[0089] In step six, the shear stirring speed of the moisture-curing prepolymer, silane coupling agent, liquid SBS and diluted matrix asphalt is 1500 r / min, and the shear stirring time is 30 min.

[0090] In step seven, the stirring speed of the aggregates of each particle size after drying is 400 r / min, and the stirring time is 90 s; the asphalt cold make-up liquid is put into the mixer and continues to be stirred at a speed of 400 r / min and a stirring time of 90 s; the magnesium phosphate cementitious material is put into the mixer and continues to be stirred at a speed of 500 r / min and a stirring time of 150 s.

[0091] Embodiment three:

[0092] According to another preferred embodiment of the magnesium phosphate-polyurethane composite wet-curing cold patch asphalt mixture and preparation method of the present invention, its material ratio, preparation process, technical principle, beneficial effects, etc. are basically the same as those of the first embodiment, except that:

[0093] The mass percentage of each substance in the cold patch asphalt mixture is as follows: 7.5wt% of base asphalt, 2wt% of magnesium phosphate gelling material, 2.5wt% of polyurethane, 0.3wt% of silane coupling agent, 0.8wt% of liquid SBS, 0.5wt% of accelerator, 2.6wt% of chain extender, 2.8wt% of diluent and 81wt% of aggregate.

[0094] The amount of the diluent added increases with the amount of the base asphalt added. Within the mass percentage range of the diluent and the base asphalt, when the amount of the base asphalt added increases by 0.5wt%, the amount of the diluent added increases by 0.5wt% accordingly, and is controlled within the range of 0.4-0.8wt%.

[0095] The sum of the added amounts of the coagulant and the chain extender increases with the increased added amount of the polyurethane. Within the mass percentage range of the coagulant, the chain extender and the polyurethane, when the added amount of the polyurethane increases by 0.5wt%, the sum of the added amounts of the coagulant and the chain extender increases by 0.7wt% accordingly, and is controlled within the range of 0.6-1wt%.

[0096] The mass percentages of the substances in the magnesium phosphate gelling material are as follows: 55 wt % of dead-burned magnesium oxide, 24 wt % of diammonium phosphate, 10 wt % of fly ash, and 11 wt % of aluminum oxide. The particle size distribution of the dead-burned magnesium oxide is between 2-10 μm; the particle size distribution of the diammonium phosphate is between 30-100 μm, wherein the mass percentage of each particle size in the diammonium phosphate is as follows: 75-100 μm accounts for 35 wt%, 50-75 μm accounts for 35 wt%, and 30-50 μm accounts for 30 wt%; the particle size distribution of the fly ash is between 20-100 μm, wherein the mass percentage of each particle size in the fly ash is as follows: 75-100 μm accounts for 35 wt%, 50-75 μm accounts for 35 wt%, and 20-50 μm accounts for 30 wt%; the particle size distribution of the aluminum oxide is between 0.5-10 μm.

[0097] The polyurethane is an adhesive synthesized from diphenylmethane-4,4'-diisocyanate as the main material; the silane coupling agent is γ-aminopropyltriethoxysilane; the mass percentage of each substance in the liquid SBS is 70wt% of solid SBS and 30wt% of organic solvent, and the organic solvent is toluene. The base asphalt is No. 70 base asphalt; the coagulant is triethylamine; the chain extender is 1,4-butanediol; and the diluent is diesel.

[0098] The aggregate includes five particle sizes, and the mass percentage of each particle size in the aggregate is: particle size 13.2-16mm accounts for 15wt%, particle size 9.5-13.2mm accounts for 27wt%, particle size 4.75-9.5mm accounts for 28wt%, particle size 2.36-4.75mm accounts for 20wt%, and particle size 0-2.36mm accounts for 10wt%. The aggregate is limestone.

[0099] In step 2, the preparation method of the magnesium phosphate gelling material comprises the following steps in order:

[0100] Step (1): according to the designed material ratio, heavy-burned magnesium oxide and aluminum oxide are placed in a mixer and stirred at room temperature, a stirring speed of 200 r / min, and a stirring time of 60 s;

[0101] Step (2): according to the designed material ratio, fly ash of various particle sizes is placed in a mixer and stirred continuously at room temperature, a stirring speed of 300 r / min, and a stirring time of 90 s;

[0102] Step (3): according to the designed material ratio, diammonium dihydrogen phosphate of each particle size is placed in a mixer and continued to be stirred. The stirring temperature is room temperature, the stirring speed is 300r / min, and the stirring time is 90s. After the stirring is completed, a mixture of the substances is obtained. Step (4): the mixture of the substances is placed in an oven for low-temperature drying. The drying temperature is 100°C and the drying time is 1h. After the drying treatment is completed, the magnesium phosphate gelling material is obtained and sealed for use.

[0103] In step three, the drying temperature of aggregates of various particle sizes is 120°C, and the drying time is 2h; the temperature in the oven is reduced to 80°C, that is, the insulation temperature of aggregates of various particle sizes is 80°C.

[0104] In step 4, the heating temperature of the base asphalt is 150°C, and the heating time is 1 hour; the shear stirring speed of the base asphalt and the diluent is 2000 r / min, and the shear stirring time is 0.5 hour.

[0105] In step six, the shear stirring speed of the moisture-curing prepolymer, silane coupling agent, liquid SBS and diluted matrix asphalt is 2000 r / min, and the shear stirring time is 20 min.

[0106] In step seven, the mixing speed of the aggregates of each particle size after drying is 500 r / min, and the mixing time is 60 s; the asphalt cold make-up liquid is put into the mixer and continues to be stirred at a speed of 500 r / min and a mixing time of 60 s; the magnesium phosphate cementitious material is put into the mixer and continues to be stirred at a speed of 800 r / min and a mixing time of 90 s.

[0107] Embodiment 4:

[0108] According to another preferred embodiment of the magnesium phosphate-polyurethane composite wet-curing cold patch asphalt mixture and preparation method of the present invention, its material ratio, preparation process, technical principle, beneficial effects, etc. are basically the same as those of the first embodiment, except that:

[0109] The mass percentage of each substance in the cold patch asphalt mixture is: 8wt% of base asphalt, 2.5wt% of magnesium phosphate cementitious material, 3wt% of polyurethane, 0.4wt% of silane coupling agent, 0.5wt% of liquid SBS, 0.8wt% of accelerator, 3.3wt% of chain extender, 3.5wt% of diluent and 78wt% of aggregate.

[0110] The amount of the diluent added increases with the amount of the base asphalt added. Within the mass percentage range of the diluent and the base asphalt, when the amount of the base asphalt added increases by 0.5wt%, the amount of the diluent added increases by 0.7wt% accordingly, and is controlled within the range of 0.4-0.8wt%.

[0111] The sum of the added amounts of the coagulant and the chain extender increases with the increased added amount of the polyurethane. Within the mass percentage range of the coagulant, the chain extender and the polyurethane, when the added amount of the polyurethane increases by 0.5wt%, the sum of the added amounts of the coagulant and the chain extender increases by 1wt% accordingly, and is controlled within the range of 0.6-1wt%.

[0112] The mass percentages of the various substances in the magnesium phosphate gelling material are as follows: 54 wt % of dead-burned magnesium oxide, 22 wt % of diammonium phosphate, 12 wt % of fly ash, and 12 wt % of aluminum oxide. The particle size distribution of the dead-burned magnesium oxide is between 2-10 μm; the particle size distribution of the diammonium phosphate is between 30-100 μm, wherein the mass percentage of each particle size in the diammonium phosphate is as follows: 75-100 μm accounts for 35 wt%, 50-75 μm accounts for 35 wt%, and 30-50 μm accounts for 30 wt%; the particle size distribution of the fly ash is between 20-100 μm, wherein the mass percentage of each particle size in the fly ash is as follows: 75-100 μm accounts for 35 wt%, 50-75 μm accounts for 35 wt%, and 20-50 μm accounts for 30 wt%; the particle size distribution of the aluminum oxide is between 0.5-10 μm.

[0113] The polyurethane is an adhesive synthesized from diphenylmethane-4,4'-diisocyanate as the main material; the silane coupling agent is vinyl triethoxysilane; the mass percentage of each substance in the liquid SBS is solid SBS 50wt%, organic solvent 50wt%, and the organic solvent is cyclohexane. The base asphalt is No. 90 base asphalt; the coagulant is dimethylaminoethyl ether; the chain extender is neopentyl glycol; and the diluent is aromatic oil.

[0114] The aggregate includes five particle sizes, and the mass percentage of each particle size in the aggregate is: particle size 13.2-16mm accounts for 13wt%, particle size 9.5-13.2mm accounts for 26wt%, particle size 4.75-9.5mm accounts for 26wt%, particle size 2.36-4.75mm accounts for 23wt%, and particle size 0-2.36mm accounts for 12wt%. The aggregate is basalt.

[0115] In step 2, the preparation method of the magnesium phosphate gelling material comprises the following steps in order:

[0116] Step (1): according to the designed material ratio, put the dead-burned magnesium oxide and aluminum oxide into a mixer and stir them at room temperature, a stirring speed of 120 r / min, and a stirring time of 85 s;

[0117] Step (2): according to the designed material ratio, fly ash of various particle sizes is placed in a mixer and stirred continuously at room temperature, a stirring speed of 220 r / min, and a stirring time of 135 s;

[0118] Step (3): according to the designed material ratio, diammonium dihydrogen phosphate of each particle size is placed in a mixer and continued to be stirred. The stirring temperature is room temperature, the stirring speed is 220r / min, and the stirring time is 135s. After the stirring is completed, a mixture of the substances is obtained. Step (4): the mixture of the substances is placed in an oven for low-temperature drying. The drying temperature is 85°C and the drying time is 1.8h. After the drying treatment is completed, the magnesium phosphate gelling material is obtained and sealed for use.

[0119] In step three, the drying temperature of aggregates of various particle sizes is 105°C, and the drying time is 2.8h; the temperature in the oven is reduced to 65°C, that is, the insulation temperature of aggregates of various particle sizes is 65°C.

[0120] In step 4, the heating temperature of the base asphalt is 135°C, and the heating time is 1.8h; the shear stirring speed of the base asphalt and the diluent is 1700r / min, and the shear stirring time is 0.9h.

[0121] In step six, the shear stirring speed of the moisture-curing prepolymer, silane coupling agent, liquid SBS and diluted matrix asphalt is 1700 r / min, and the shear stirring time is 28 min.

[0122] In step seven, the stirring speed of the aggregates of each particle size after drying is 430 r / min, and the stirring time is 85 s; the asphalt cold make-up liquid is put into the mixer and continued to be stirred at a stirring speed of 430 r / min, and the stirring time is 85 s; the magnesium phosphate cementitious material is put into the mixer and continued to be stirred at a stirring speed of 600 r / min, and the stirring time is 140 s.

[0123] Embodiment five:

[0124] According to another preferred embodiment of the magnesium phosphate-polyurethane composite wet-curing cold patch asphalt mixture and preparation method of the present invention, its material ratio, preparation process, technical principle, beneficial effects, etc. are basically the same as those of the first embodiment, except that:

[0125] The mass percentage of each substance in the cold patch asphalt mixture is: 8.5wt% of base asphalt, 3wt% of magnesium phosphate cementitious material, 3.5wt% of polyurethane, 0.4wt% of silane coupling agent, 1wt% of liquid SBS, 1wt% of accelerator, 3.7wt% of chain extender, 3.9wt% of diluent and 75wt% of aggregate.

[0126] The amount of the diluent added increases with the amount of the base asphalt added. Within the mass percentage range of the diluent and the base asphalt, when the amount of the base asphalt added increases by 0.5wt%, the amount of the diluent added increases by 0.4wt% accordingly, and is controlled within the range of 0.4-0.8wt%.

[0127] The sum of the added amounts of the coagulant and the chain extender increases with the increased added amount of the polyurethane. Within the mass percentage range of the coagulant, the chain extender and the polyurethane, when the added amount of the polyurethane increases by 0.5wt%, the sum of the added amounts of the coagulant and the chain extender increases by 0.6wt% accordingly, and is controlled within the range of 0.6-1wt%.

[0128] The mass percentages of various substances in the magnesium phosphate gelling material are as follows: 52 wt % of dead-burned magnesium oxide, 20 wt % of diammonium phosphate, 14 wt % of fly ash and 14 wt % of aluminum oxide. The particle size distribution of the dead-burned magnesium oxide is between 2-10 μm; the particle size distribution of the diammonium phosphate is between 30-100 μm, wherein the mass percentage of each particle size in the diammonium phosphate is as follows: 75-100 μm accounts for 35 wt%, 50-75 μm accounts for 35 wt%, and 30-50 μm accounts for 30 wt%; the particle size distribution of the fly ash is between 20-100 μm, wherein the mass percentage of each particle size in the fly ash is as follows: 75-100 μm accounts for 35 wt%, 50-75 μm accounts for 35 wt%, and 20-50 μm accounts for 30 wt%; the particle size distribution of the aluminum oxide is between 0.5-10 μm.

[0129] The polyurethane is an adhesive synthesized from diphenylmethane-4,4'-diisocyanate as the main material; the silane coupling agent is vinyl triethoxysilane; the mass percentage of each substance in the liquid SBS is 65wt% of solid SBS and 35wt% of organic solvent, and the organic solvent is cyclohexane. The base asphalt is No. 90 base asphalt; the coagulant is dimethylaminoethyl ether; the chain extender is neopentyl glycol; and the diluent is aromatic oil.

[0130] The aggregate includes five particle sizes, and the mass percentage of each particle size in the aggregate is: particle size 13.2-16mm accounts for 12wt%, particle size 9.5-13.2mm accounts for 29wt%, particle size 4.75-9.5mm accounts for 29wt%, particle size 2.36-4.75mm accounts for 20wt%, and particle size 0-2.36mm accounts for 10wt%. The aggregate is basalt.

[0131] In step 2, the preparation method of the magnesium phosphate gelling material comprises the following steps in order:

[0132] Step (1): according to the designed material ratio, put the dead-burned magnesium oxide and aluminum oxide into a mixer and stir them at room temperature, a stirring speed of 180 r / min, and a stirring time of 65 s;

[0133] Step (2): according to the designed material ratio, fly ash of various particle sizes is placed in a mixer and stirred continuously at room temperature, a stirring speed of 280 r / min, and a stirring time of 110 s;

[0134] Step (3): according to the designed material ratio, diammonium dihydrogen phosphate of each particle size is placed in a mixer and continuously stirred. The stirring temperature is room temperature, the stirring speed is 280 r / min, and the stirring time is 110 s. After the stirring is completed, a mixture of the substances is obtained. Step (4): the mixture of the substances is placed in an oven for low-temperature drying. The drying temperature is 95° C. and the drying time is 1.2 h. After the drying is completed, a magnesium phosphate gelling material is obtained and sealed for later use.

[0135] In step three, the drying temperature of aggregates of various particle sizes is 115°C, and the drying time is 2.2h; the temperature in the oven is reduced to 75°C, that is, the insulation temperature of aggregates of various particle sizes is 75°C.

[0136] In step 4, the heating temperature of the base asphalt is 145°C, and the heating time is 1.2h; the shear stirring speed of the base asphalt and the diluent is 1900r / min, and the shear stirring time is 0.7h.

[0137] In step six, the shear stirring speed of the moisture-curing prepolymer, silane coupling agent, liquid SBS and diluted matrix asphalt is 1900 r / min, and the shear stirring time is 22 min.

[0138] In step seven, the stirring speed of the aggregates of each particle size after drying is 480 r / min, and the stirring time is 70 s; the asphalt cold make-up liquid is put into the mixer and continued to be stirred at a stirring speed of 480 r / min, and the stirring time is 70 s; the magnesium phosphate cementitious material is put into the mixer and continued to be stirred at a stirring speed of 750 r / min, and the stirring time is 110 s.

[0139] The cold patch asphalt mixtures prepared in the above five embodiments were tested for water damage resistance, high temperature performance, low temperature resistance, cohesion (for characterizing early strength) and curing time, and the test equipment, test environment, test conditions, sample shape and size used were the same.

[0140] The cold patch asphalt mixtures prepared in the above five embodiments were subjected to the immersion Marshall test, freeze-thaw splitting test, rutting test, beam low-temperature bending test, cohesion test, curing time measurement, etc. Each test must comply with the corresponding test operation specifications, such as the "Test Procedures for Asphalt and Asphalt Mixtures for Highway Engineering" (JTG E20-2011). The test equipment, test environment, test conditions, sample shape and size used in each test are the same.

[0141] The immersion Marshall test and freeze-thaw splitting test are used to test the water damage resistance of cold-patch asphalt mixture, which are characterized by the residual stability after immersion and the freeze-thaw splitting strength ratio respectively; the rutting test (60℃, 0.7MPa) is used to test the high temperature performance of cold-patch asphalt mixture, which is characterized by the dynamic stability; the beam low temperature bending test (-10℃) is used to test the low temperature resistance of cold-patch asphalt mixture, which is characterized by the flexural tensile strength, ultimate flexural tensile strain, and flexural stiffness modulus; the cohesion test is used to test the early strength of cold-patch asphalt mixture, which is characterized by the damage rate; the curing speed of cold-patch asphalt mixture is characterized by measuring the curing time. The test results are shown in Table 1.

[0142] Table 1 Performance test results of cold patch asphalt mixture

[0143]

[0144] It can be seen from the test results that the cold-patch asphalt mixture prepared in the above embodiment has the characteristics of fast curing speed, high early strength, good stability, etc. The good stability is reflected in the strong resistance to water damage, good high temperature performance, strong resistance to low temperature, etc. The comprehensive performance can meet the performance requirements of hot-mix asphalt mixture, and the potholes, cracks and damage on the road surface can be quickly opened to traffic after repair without affecting road traffic.

[0145] The aggregates, base asphalt, various substances used to prepare magnesium phosphate cementitious materials, solid SBS and other substances used in the above embodiments were purchased from Beijing Municipal Road and Bridge Building Materials Group Co., Ltd., and polyurethane, silane coupling agent, organic solvent, coagulant, chain extender, diluent and other substances were purchased from Aladdin Reagent Co., Ltd.

[0146] Special note: The technical solution of the present invention involves many parameters, and the synergistic effects between the various parameters need to be comprehensively considered to obtain the beneficial effects and significant progress of the present invention. Moreover, the value ranges of the various parameters in the technical solution are obtained after a large number of experiments. For each parameter and the combination of each parameter, the inventor has recorded a large amount of experimental data. Due to space limitations, the specific experimental data will not be disclosed here.

[0147] It is not difficult for those skilled in the art to understand that the magnesium phosphate-polyurethane composite wet-curing cold-patch asphalt mixture and preparation method of the present invention include any combination of the invention content and specific implementation methods of the above-mentioned invention specification and the various parts shown in the drawings. Due to the limited space and to make the specification concise, the various schemes composed of these combinations are not described one by one. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A magnesium phosphate-polyurethane composite wet-curing cold-patch asphalt mixture, characterized in that: The mass percentage of each substance in the cold patch asphalt mixture is as follows: base asphalt 6.5-8.5wt%, magnesium phosphate gelling material 1-3wt%, polyurethane 1.5-3.5wt%, silane coupling agent 0.1-0.5wt%, liquid SBS 0.3-1wt%, accelerator 0.1-1wt%, chain extender 1.5-4wt%, diluent 1.7-4wt%, aggregate 75-87wt%, and the sum of the contents of each substance is 100wt%.

2. The magnesium phosphate-polyurethane composite wet-curing cold-patch asphalt mixture according to claim 1, characterized in that: The amount of the diluent added increases with the amount of the base asphalt added. Within the mass percentage range of the diluent and the base asphalt, when the amount of the base asphalt added increases by 0.5wt%, the amount of the diluent added increases by 0.4-0.8wt% accordingly.

3. The magnesium phosphate-polyurethane composite wet-curing cold-patch asphalt mixture according to claim 2, characterized in that: The sum of the added amounts of the coagulant and the chain extender increases with the increased added amount of the polyurethane. Within the mass percentage range of the coagulant, the chain extender and the polyurethane, when the added amount of the polyurethane increases by 0.5wt%, the sum of the added amounts of the coagulant and the chain extender increases by 0.6-1wt% accordingly.

4. The magnesium phosphate-polyurethane composite wet-curing cold-patch asphalt mixture according to claim 3, characterized in that: The mass percentages of the various substances in the magnesium phosphate gelling material are as follows: 50-55wt% of dead-burned magnesium oxide, 18-24wt% of diammonium phosphate, 10-16wt% of fly ash, and 10-16wt% of aluminum oxide. The sum of the contents of the various substances is 100wt%.

5. The magnesium phosphate-polyurethane composite wet-curing cold-patch asphalt mixture according to claim 4, characterized in that: The particle size distribution of the dead-burned magnesium oxide is between 2-10 μm; the particle size distribution of the diammonium phosphate is between 30-100 μm, wherein the mass percentage of each particle size in the diammonium phosphate is as follows: 75-100 μm accounts for 35 wt%, 50-75 μm accounts for 35 wt%, and 30-50 μm accounts for 30 wt%; the particle size distribution of the fly ash is between 20-100 μm, wherein the mass percentage of each particle size in the fly ash is as follows: 75-100 μm accounts for 35 wt%, 50-75 μm accounts for 35 wt%, and 20-50 μm accounts for 30 wt%; the particle size distribution of the aluminum oxide is between 0.5-10 μm.

6. The magnesium phosphate-polyurethane composite wet-curing cold-patch asphalt mixture according to claim 5, characterized in that: The polyurethane is an adhesive synthesized from diphenylmethane-4,4'-diisocyanate as the main material; the silane coupling agent is γ-aminopropyltriethoxysilane and / or vinyltriethoxysilane; the mass percentage of each substance in the liquid SBS is 40-70wt% of solid SBS and 30-60wt% of organic solvent, and the organic solvent includes any one or more of toluene, cyclohexane and acetone.

7. The magnesium phosphate-polyurethane composite wet-curing cold-patch asphalt mixture according to claim 6, characterized in that: The base asphalt is No. 70 base asphalt and / or No. 90 base asphalt; the accelerator includes any one or more of triethylamine, N,N-dimethylcyclohexylamine, and bis(dimethylaminoethyl) ether; the chain extender includes any one or more of 1,4-butanediol, neopentyl glycol, ethylene glycol, diethylene glycol, and 1,4-cyclohexanedimethanol; the diluent includes any one or more of diesel, kerosene, gasoline, solvent oil, aromatic oil, and xylene.

8. The magnesium phosphate-polyurethane composite wet-curing cold-patch asphalt mixture according to claim 7, characterized in that: The aggregate includes five particle sizes, and the mass percentage of each particle size in the aggregate is: particle size 13.2-16mm accounts for 10-15wt%, particle size 9.5-13.2mm accounts for 25-30wt%, particle size 4.75-9.5mm accounts for 25-30wt%, particle size 2.36-4.75mm accounts for 20-25wt%, and particle size 0-2.36mm accounts for 10-15wt%. The aggregate includes any one or more of limestone, basalt, granite, and diabase.

9. A method for preparing a magnesium phosphate-polyurethane composite wet-curing cold-patch asphalt mixture, characterized in that: The magnesium phosphate-polyurethane composite wet-curing cold-patch asphalt mixture according to any one of claims 1 to 8 comprises the following steps in order: Step 1: Weigh all raw materials according to the designed material ratio; Step 2: preparing magnesium phosphate gelling material according to the designed material ratio and process parameters; Step 3: Put the aggregates of each particle size into the oven for drying. After the drying process is completed, reduce the temperature in the oven to a certain temperature, and keep the aggregates of each particle size at the reduced temperature for later use; Step 4: Put the matrix asphalt into a container, and then put the container containing the matrix asphalt into an oven for heating to completely melt the matrix asphalt; after the heating is completed, take out the container containing the matrix asphalt from the oven, and put the completely melted matrix asphalt and the diluent into a high-speed shearing machine for shearing and stirring until the matrix asphalt and the diluent are completely melted to obtain diluted matrix asphalt; Step 5: Put polyurethane, coagulant and chain extender into a container and mix them evenly to obtain a moisture-curable prepolymer; put solid SBS and organic solvent into another container and mix them evenly to obtain liquid SBS; Step 6: Put the wet curing prepolymer, silane coupling agent and liquid SBS into a high-speed shearing machine, and shear and stir them together with the diluted matrix asphalt until they are completely blended to obtain asphalt cold patch liquid; Step seven: Put the dried aggregates of various particle sizes into a mixer for stirring. After stirring for a certain period of time, put the asphalt cold patch liquid into the mixer and continue stirring while keeping the stirring speed unchanged. After stirring for a certain period of time, increase the stirring speed and put the magnesium phosphate cementitious material into the mixer and continue stirring to obtain a magnesium phosphate-polyurethane composite wet-curing cold patch asphalt mixture.

10. The method for preparing the magnesium phosphate-polyurethane composite wet-curing cold-patch asphalt mixture according to claim 9, characterized in that: In step 2, the preparation method of the magnesium phosphate gelling material comprises the following steps in order: Step (1): according to the designed material ratio, put the dead-burned magnesium oxide and aluminum oxide into a mixer and stir them. The stirring temperature is room temperature, the stirring speed is 100-200 r / min, and the stirring time is 60-90 s; Step (2): according to the designed material ratio, fly ash of various particle sizes is placed in a mixer and continuously stirred at room temperature, a stirring speed of 200-300 r / min, and a stirring time of 90-150 s; Step (3): according to the designed material ratio, diammonium dihydrogen phosphate of each particle size is placed in a mixer and continuously stirred. The stirring temperature is room temperature, the stirring speed is 200-300 r / min, and the stirring time is 90-150 s. After the stirring is completed, a mixture of the substances is obtained; Step (4): placing the mixture of the substances into an oven for low-temperature drying, the drying temperature being 80-100° C., and the drying time being 1-2 h. After the drying process is completed, a magnesium phosphate gelling material is obtained, which is sealed for later use; In step 3, the drying temperature of aggregates of various particle sizes is 100-120°C, and the drying time is 2-3h; the temperature in the oven is reduced to 60-80°C, that is, the insulation temperature of aggregates of various particle sizes is 60-80°C; In step 4, the heating temperature of the base asphalt is 130-150°C, and the heating time is 1-2h; the shear stirring speed of the base asphalt and the diluent is 1500-2000r / min, and the shear stirring time is 0.5-1h; In step 6, the shear stirring speed of the moisture-curing prepolymer, silane coupling agent, liquid SBS and diluted matrix asphalt is 1500-2000 r / min, and the shear stirring time is 20-30 min; In step seven, the stirring speed of the aggregates of each particle size after drying is 400-500r / min, and the stirring time is 60-90s; the asphalt cold make-up liquid is put into the mixer and continued to be stirred at a speed of 400-500r / min, and the stirring time is 60-90s; the magnesium phosphate cementitious material is put into the mixer and continued to be stirred at a speed of 500-800r / min, and the stirring time is 90-150s.

Citation Information

Patent Citations

  • Moisture cured polyurethane modified cold-mixed asphalt and preparation method thereof

    CN113248938A

  • Reactive dilution type regenerated cold patch material suitable for severe rain and snow environment and preparation method of reactive dilution type regenerated cold patch material

    CN117024054A

Cited By

  • Normal-temperature bio-based asphalt cold patch material and preparation method thereof

    CN121044836A